Association between cirrhosis and herpes zoster in a cohort study in Taiwan. Issue 11 (9th August 2021) - Lai, Shih‐Wei; Liao, Kuan‐Fu; Lin, Cheng‐Li; Liu, Chiu‐Shong; Hwang, Bing‐Fang
Abstract: Objectives: The aim of the study was to assess if an association exists between cirrhosis and herpes zoster in Taiwan. Methods: A retrospective cohort study was designed to analyse the 2000‐2013 claim dataset of 1 million insured residents who were randomly sampled from the Taiwan National Health Insurance Program. In total, 16 190 subjects aged 20‐84 years old with newly diagnosed cirrhosis since 2000 to 2012 were identified as the cirrhosis group and 16 190 sex‐ and age‐matched subjects without cirrhosis were selected as the non‐cirrhosis group. Both cirrhosis and non‐cirrhosis groups were followed until a new diagnosis of herpes zoster was made or until the end of 2013. The multivariable Cox proportional hazard regression model was applied to calculate the hazard ratio (HR) and 95% confidence interval (CI) for herpes zoster associated with cirrhosis. Results: The incidence rate of herpes zoster was 1.08‐fold greater in the cirrhosis group than the non‐cirrhosis group (8.33 vs 7.69 per 1000 person‐years, 95%CI 1.02‐1.15). After adjusting for confounders, the adjusted HR of herpes zoster was 1.11 (95% CI 1.004‐1.24) for the cirrhosis group compared with the non‐cirrhosis group. The adjusted HR increased to 1.33 (95% CI 1.02‐1.74) for the decompensated cirrhosis group compared with the non‐cirrhosis group. Conclusions: Cirrhosis is associated with a small but significant increase in the risk of herpes zoster. Given that the risk of herpes zoster is small and the expense of herpes zoster vaccination is high, whether cirrhotic persons need to be vaccinated should assess the balance of cost and benefit.